Characterization of cadmium sulphide (CdS) thin film deposited by spray pyrolysis technique - Dhawankar, Sachin H.; Suryavanshi, Bhagwat. M. (International Journal of Physical Research, 2016)
Cadmium sulphide thin film is deposited on the glass slide using aqueous solution of cadmium chloride and thiourea by using spray pyrolysis deposition technique at temperature of 4000C. Structural, optical and electrical properties of deposited CdS thin film are investigated. Optical studied of CdS thin film is characterized by using UV –Visible Spectrophotometer in the visible region (380 – 1000 nm). The energy Band gap of CdS thin film is obtained in the present work at 2.3 eV. Thickness of CdS thin film is determined by using weight difference density method. Absorption coefficient and extinction coefficient of CdS thin film are studied in the present work. Structural characterization of CdS thin is done by using X-Ray diffractometer. XRD Pattern analysis showed that the CdS thin film is mixed phases of cubic and hexagonal structure. Using four probe methods the electrical resistivity and electrical conductivity of CdS thin film are studied.